2015
DOI: 10.1242/jeb.116723
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory consequences of salt loading in the lizard, Pogona vitticeps

Abstract: Previous research has demonstrated that dehydration increases the threshold temperature for panting and decreases the thermal preference of lizards. Conversely, it is unknown whether thermoregulatory responses such as shuttling and gaping are similarly influenced. Shuttling, as an active behavioural response, is considered one of the most effective thermoregulatory behaviours, whereas gaping has been proposed to be involved in preventing brain over-heating in lizards. In this study we examined the effect of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“… 8,9 Most anurans, however, offer little or no resistance to evaporative water loss. 9-12 It is known that thermoregulatory adjustments need to accommodate the potentially conflicting compromises related to water balance 13 and the prominent tendency of amphibians to lose water is thought to prevent a more efficient regulation of T b . As a consequence, amphibians, and particularly terrestrial anurans, may have their activities limited, daily and seasonally, by the availability of adequate thermal microhabitats that allow for thermoregulation without serious consequences to water balance.…”
Section: Introductionmentioning
confidence: 99%
“… 8,9 Most anurans, however, offer little or no resistance to evaporative water loss. 9-12 It is known that thermoregulatory adjustments need to accommodate the potentially conflicting compromises related to water balance 13 and the prominent tendency of amphibians to lose water is thought to prevent a more efficient regulation of T b . As a consequence, amphibians, and particularly terrestrial anurans, may have their activities limited, daily and seasonally, by the availability of adequate thermal microhabitats that allow for thermoregulation without serious consequences to water balance.…”
Section: Introductionmentioning
confidence: 99%
“…In lepidosaurs, one mechanism that triggers this decrease in thermal preference is the neuropeptide arginine vasotocin (AVT), secreted by the pars nervosa of the brain in response to high blood sodium ion concentration (Bradshaw et al, 2007). There has even been past work on bearded dragons specifically to suggest that they thermoregulate differently when they are dehydrated compared with when they are hydrated (da Silveira Scarpellini et al, 2015). However, da Silveira Scarpellini et al (2015) demonstrated that dehydrated bearded dragons do not strictly exhibit an anapyrexia (i.e.…”
Section: Thermal Preferencementioning
confidence: 99%
“…There has even been past work on bearded dragons specifically to suggest that they thermoregulate differently when they are dehydrated compared with when they are hydrated (da Silveira Scarpellini et al, 2015). However, da Silveira Scarpellini et al (2015) demonstrated that dehydrated bearded dragons do not strictly exhibit an anapyrexia (i.e. lowered thermal preference) in response to dehydration.…”
Section: Thermal Preferencementioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, as the heat load progresses, thermal tachypnea wanes into thermal hyperventilation, a deep and slow breathing pattern oriented to boost heat dissipation at the expense of blood gas homeostasis (Mortola and Maskrey, 2011). Interestingly, several lizard species also use thermal tachypnea or gaping (increased heat loss with opened mouth) to protect the brain from a rise in temperature (Tattersall et al, 2006;Scarpellini et al, 2015).…”
Section: Introductionmentioning
confidence: 99%